1982
DOI: 10.2113/gsecongeo.77.6.1439
|View full text |Cite
|
Sign up to set email alerts
|

The petrogenesis of a platiniferous dunite pipe in the Bushveld Complex; infiltration metasomatism by a chloride solution

Abstract: The Driekop dunite pipe crosscuts part of the noritic layered sequence of the upper critical zone in the eastern Bushveld Complex. The central orebody of the pipe contains platinumgroup minerals, base metal sulfides, magnetite, and iron-rich olivine. The country rock forms a collapse structure around the pipe, with the layered sequence becoming almost vertical near the contact with the pipe.It is proposed that a high-temperature chloride solution flowed through irregular channelways along a structural weakness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
2

Year Published

1986
1986
2009
2009

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(49 citation statements)
references
References 12 publications
3
44
0
2
Order By: Relevance
“…It has been suggested that the pipes are feeders of mineralization into the stratiform reefs (Schiffries 1982, Stumpfl & Rucklidge 1982. Figure 13 shows that the PGE content and relative proportions do not appear to be influenced by proximity to a pipe, although the mineral assemblage was.…”
Section: Discussionmentioning
confidence: 98%
“…It has been suggested that the pipes are feeders of mineralization into the stratiform reefs (Schiffries 1982, Stumpfl & Rucklidge 1982. Figure 13 shows that the PGE content and relative proportions do not appear to be influenced by proximity to a pipe, although the mineral assemblage was.…”
Section: Discussionmentioning
confidence: 98%
“…Il existe deux types de pegmatites ultramafiques riches en oxyde : i-pegmatite à olivine et clinopyroxène, et ii-pegmatite riche en oxydes (Scoon et Mitchell, 1994). Scoon et Mitchell (1994) La même origine métasomatique similaire à celle proposée par Schiffries (1982) a été suggérée par Ross (1985) pour les dunites à péridotites riches en oxydes et de granulométrie grossière à la base de la série litée de Duluth. Ross (1985) …”
Section: Origine Métasomatique Des Oui ??unclassified
“…Conversely, the samples of discordant wehrlite have low Cl contents and so appear not to have been affected. On the basis of the absence of alteration in these wehrlites and the low temperature at which the hibbingite was formed in the layered rocks, we conclude that these discordant bodies are not Cl-rich, as proposed by Schiffries (1982), nor likely to have contained this Cl-rich fluid.…”
Section: Discussionmentioning
confidence: 57%